Progress and setbacks in the neo-developmentalist agenda of public policy in Brazil - José Marcos Nayme Novelli (University of Bath, Centre for Development Studies (CDS), 2016)
This text's purpose is to analyze the progress and setbacks in public policies during PT (Partido dos Trabalhadores) governments (2003-2015), especially macroeconomic, industrial, social and income-related policies, as well as their relation to the neo-developmentalist agenda. My overall argument is based on the assumption that coalition and ideas matter. Ideas are important to build and to destroy coalitions. Coalitions formed in society are important because they support the adoption of public policies. The developmentalist coalition (1930's-1980's) supported a set of policies that led to the industrialization of the Brazilian economy. When this coalition entered into a crisis (1980's-1990's), it has been replaced by the disinflationary-reformist coalition (post-1994), which supported the application of disinflationary policies and inflation control, as well as the liberalization reforms (neoliberal). This coalition remained very active in PT governments, especially in relation of macroeconomic policy, whose policies have never moved away from the economic ideas which unify that coalition. The austerity policies adopted by the government in 2015 is an example of the importance and political weight of this coalition. However, the governments of PT - backed by a new coalition (neo-developmentalist) - sought to reorient industrial, social and income policies. In the case of industrial policy, its effects were mitigated by maintaining a disinflationary macroeconomic policy based on the appreciation of the Brazilian currency (real). As for social and income policies there was an undeniable progress, despite these policies have always been under the attack of the disinflationary-reformist coalition.
Keywords: 330; Politics; public policy; Latin America